2020
DOI: 10.14569/ijacsa.2020.0111150
|View full text |Cite
|
Sign up to set email alerts
|

RHEM: A Robust Hybrid Ensemble Model for Students’ Performance Assessment on Cloud Computing Course

Abstract: Creating tools, such as a prediction model to assist students in a traditional or virtual setting, is an essential activity in today's educational climate. The early stage towards incorporating these predictive models using techniques of machine learning focused on predicting the achievement of students in terms of the grades obtained. The research aim is to propose a robust hybrid ensemble model (RHEM) that can warn at-risks students (on Cloud Computing course) of their likely outcomes at the early semester a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Access to internet, Age, Economic dependence, Employment status, Ethnicity, Family Highest Education Level, Family income, Family size, Gender, Health status, House to university distance, Lives in town or village, Marital Status, Nationality, Parents job, Parents occupation, Parents qualification, Parent status, Total income [17], [22], [23], [26], [28]- [31], [35], [38], [41]- [43], [46], [48]- [55], [57]- [60], [63]- [65], [67], [68], [70]- [77] Leonardo…”
Section: Factor Variables Authors Who Consider Variables Of This Factormentioning
confidence: 99%
See 2 more Smart Citations
“…Access to internet, Age, Economic dependence, Employment status, Ethnicity, Family Highest Education Level, Family income, Family size, Gender, Health status, House to university distance, Lives in town or village, Marital Status, Nationality, Parents job, Parents occupation, Parents qualification, Parent status, Total income [17], [22], [23], [26], [28]- [31], [35], [38], [41]- [43], [46], [48]- [55], [57]- [60], [63]- [65], [67], [68], [70]- [77] Leonardo…”
Section: Factor Variables Authors Who Consider Variables Of This Factormentioning
confidence: 99%
“…Table 4 shows the variables found that belong to the factor and the authors who used some of these for the development of their models. [22], [23], [26], [28]- [30], [35], [38]- [40], [42]- [44], [46], [49]- [52], [55], [57], [58], [60], [61], [63]- [68],…”
Section: Academic Management Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Voting is also known for its heterogeneous nature where classifiers comprise different algorithms which are used to predict the final outcome. It creates two or more models and each of them make their predictions [36]. It is based on an aggregating network that is used to determine the weights' mean.…”
Section: Votingmentioning
confidence: 99%